Czynniki warunkujące jakość oraz ich wpływ na podejmowanie decyzji nabywczych na rynku gastronomicznym - Grębowiec, Mariusz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
The aim of this article was to gauge importance of quality, including quality assuring systems in purchasing decisions making on gastronomic market. In the thesis primary and secondary methods of research were used. Within the framework of secondary research the following issues were presented: the very idea of quality, quality management in food sector as well as the characteristics of modern customer and the analysis of gastronomic market in Poland. Primary research was based on a survey among customers of food offered on gastronomic market.